The cross-sectional association between vasomotor symptoms and hemostatic parameter levels in postmenopausal women. Issue 4 (April 2017) - Harrington, Laura B.; Blondon, Marc; Cushman, Mary; Kaunitz, Andrew M.; Rossouw, Jacques E.; Allison, Matthew A.; Martin, Lisa W.; Johnson, Karen C.; Rosing, Jan; Woods, Nancy F.; LaCroix, Andrea Z.; Heckbert, Susan R.; et al.
Abstract: Objective: Vasomotor symptoms (VMS) may be a marker of cardiovascular risk. We aimed to evaluate the cross-sectional association of VMS presence and severity with hemostatic parameter levels measured at baseline among Women's Health Initiative (WHI) Hormone Therapy trial postmenopausal participants. Methods: This cross-sectional analysis included 2, 148 postmenopausal women with measures of VMS presence and severity reported in the 4 weeks before WHI baseline, who were not using warfarin or hormone therapy and for whom the following baseline hemostatic parameters were measured within the WHI Cardiovascular Disease Biomarker Case-Control Study: antithrombin, plasminogen activator inhibitor-1, protein C antigen, total and free protein S antigen, total and free tissue factor pathway inhibitor, D-dimer, normalized activated protein C sensitivity ratio, and thrombin generation. Using multiple linear regression, we estimated the adjusted average difference in each hemostatic parameter associated with VMS presence and severity. A multiple comparisons-corrected P value was computed using the P-min procedure to determine statistical significance of our smallest observed P value. Results: Women were 67 years of age on average and 33% reported VMS presence at baseline. There was some suggestion that VMS presence may be associated with a −0.34 adjusted difference in normalized activated protein C sensitivity ratio compared with no VMS (95% CI, −0.60 to −0.087; P = 0.009), but this association was not significant after correction for multiple comparisons ( P = 0.073). VMS presence or severity was not significantly associated with the other hemostatic parameters. Conclusions: We found no convincing evidence that VMS presence or severity was associated with levels of hemostatic parameters among postmenopausal women. Abstract : Supplemental Digital Content is available in the text